Impact of alternative histopathology protocols in the dermatopathology laboratory: A prospective quality improvement study. (24th February 2023) - Hammond, Alexander; Covey, Sarah; Guo, Wanru; Gregory, Scott; Bender, Nicole R.; Motaparthi, Kiran; Walker, Addie
Abstract: Background: Histopathology protocols for processing dermatopathology specimens vary among laboratories. Objective: To determine an optimal histopathology protocol to minimize cost and turnaround time (TAT) for biopsy specimens in a dermatopathology laboratory. Methods: A prospective, 4‐month study compared the mean cost and TAT of producing one versus two initial H&E slides, and zero versus three unstained slides that could be used for frequently used special or immunohistochemical (IHC) stains. Results: For all cases, cost was lower for one versus two initial H&E slides, with an insignificant increase in TAT. Producing three vs zero unstained slides incurred higher cost, with no reduction in TAT. In a subset of cases in which frequently used special or IHC stains were performed, cost and TAT were optimized by producing one initial H&E and three unstained slides. Conclusion: A protocol of one initial H&E slide and zero unstained slides optimizes cost and TAT in our dermatopathology laboratory. Pigmented lesions and inflammatory dermatoses may benefit from the addition of unstained slides. Further study is needed to quantify this benefit and evaluate for other cases for which an alternative protocol is advantageous.